Low Pulse Pressure After Acute Ischemic Stroke is Associated With Unfavorable Outcomes: The Taiwan Stroke Registry - Sung‐Chun Tang; Jiu‐Haw Yin; Chung‐Hsiang Liu; Ming‐Hui Sun; Jiunn‐Tay Lee; Yu Sun; Chih‐Shan Hsu; Mu‐Chien Sun; Ching‐Huang Lin; Chih‐Hung Chen; Li‐Ming Lien; Chih‐Hsin Muo; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2017)
BackgroundPulse pressure (PP) is related to cardiac function, arterial stiffness, fluid status, and vascular events. This study aimed to explore the prognostic role of PP upon admission in patients with acute ischemic stroke (AIS) based on a nation‐wide stroke registry. Methods and ResultsWe evaluated the association between PP upon admission and outcomes 3 months after a stroke in patients who had an AIS registered in the Taiwan Stroke Registry, including 56 academic and community hospitals between 2006 and 2013. Three months after the stroke, unfavorable outcomes were defined using a modified Rankin scale of 3 to 6. Of 33 530 patients (female, 40.6%; mean age, 68.8±13.3 years) who had an AIS, PP upon admission had a reverse J‐curve association with an unfavorable outcome. After adjusting for clinical variables, including AIS subtypes, initial National Institutes of Health Stroke Scale, and systolic and diastolic blood pressure upon admission, a PP of <50 mm Hg was associated with unfavorable outcomes (P<0.0001). Compared with patients with a PP of 50 to 69 mm Hg, the odds ratios for unfavorable outcomes were 1.24 (95% CI, 1.14–1.36) with a PP of 30 to 49 mm Hg and 1.85 (95% CI, 1.50–2.28) with a PP of <30 mm Hg. Moreover, the prognostic impact of PP upon admission was similar across all AIS subtypes. ConclusionsLow PP upon admission was associated with unfavorable patient outcomes in AIS.